PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIBEL INTERVENING PADA PERUSAHAAN SUB SEKTOR SEMEN - Tua Hasudungan Pardosi, Douglas; Siagian, Harlyn L. (JEA17: Jurnal Ekonomi Akuntansi, 2021)
In observation of this research is to analyze and examine the influence of profitability on firm value with capital structure as an intervention variable. The authors use a sample of companies sub-cement sector listed on the Indonesia Stock Exchange (IDX) as many as 30 samples from 6 companies from the 2016-2020 period. Testing is also done through sampling techniques purposive sampling and assessment that has been done by the author. Some testing is done by processing the data with the cast multiple regression test and test of Sobel to find the hypothesis in research. By doing this test, then obtained the result that in the regression test variables affect profitability capital structure because the results of the significance of the low with the results of 0.000 from the boundary of the significance determined as 0.05. On the structure of the capital is also not seen any influence with the result that 0.11978 that where such a result is higher than the significant level 0.05. Subsequent testing with the test of Sobel shows if the variable profitability of the variable the value of the company with capital structure as an intervening variable does not prove the existence of the element of mediation because in the testing of the obtained results 0.80 smaller than the limit significantly by 1.96.